Moral feelings, love and freedom. An examination of Peter F. Strawson’s compatibilism - Ortiz, Eduardo (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Arguing in support of the central place that love has in our human experience, this article tries to revision the compatibilist move in favor of moral sentiments that Strawson does offer in his seminal paper «Freedom and Resentment» (1962). It tries to cope along these lines with some objections addressed against the compatibilist Strawsonian solution to the free will discussion and also to calm a justified libertarian complaint.